Blood antioxidant and oxidative stress biomarkers acute responses to a 1000-m kayak sprint in elite male kayakers - Teixeira, V. H.; Valente, H. F.; Casal, S. I.; Marques, F. P.; Moreira, P. A. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: This study aimed to investigate the response of blood antioxidants and biomarkers of lipid peroxidation, muscle damage and inflammation to a 1000m kayak trial in elite male kayakers. Methods: Enzymatic (superoxide dismutase [SOD], glutathione reductase [Gr] and glutathione peroxidase [GPx] activities) and non-enzymatic (total antioxidant status [TAS], uric acid, a-tocopherol, a-carotene, ß-carotene, lycopene and lutein and zeaxanthin) antioxidants, thiobarbituric acid reactive substances (TBARS), creatine kinase (CK), interleukin-6 (IL-6) and cortisol were determined in 15 elite male kayakers before and 15 min after a 1000-m kayak simulated race. Results: Both enzymatic and non-enzymatic antioxidants were unaffected by exercise, with the exception of a-carotene which decreased (P=0.013). Uric acid levels were incremented following exercise (P=0.016). The acute exercise resulted in a significant decrease in TAS (P=0.001) and in an increase in CK (P=0.023), TBARS (PConclusion: Our study suggests that a 1000-m kayak simulated race induces oxidative stress and damage in highly-trained kayakers.